Designing A Boost Converter to Maintain PV Output Under Different Irradiance Levels - Quek, Christopher Shou Hin; Mohamad Nor, Ahmad Fateh (Evolution in Electrical and Electronic Engineering, 2024)
The photovoltaic (PV) system is one of the most widely utilised renewable energy sources in the process of producing electricity. The incompatibility of the PV panels’ performance as a result of climate change is a disadvantage of the system. Predicting the PV system’s ideal power output at various irradiance levels is essential. The goal of this project is to improve the efficiency and stability of photovoltaic (PV) panels in renewable energy systems by designing and evaluating boost converter designs for it. The project describes the issue of variable irradiance levels and their effect on PV production, which demands the construction of adjustable boost converters. Two designs are investigated: one using a MOSFET driven by a pulse generator and the other using an IGBT controlled by PWM. Through simulation and analysis, the MOSFET arrangement shows excellent performance, constantly reaching high efficiency and nearly matching expected to power outputs. This finding emphasises the importance of component selection and control methods in booster converter design. The study closes by selecting the MOSFET arrangement as the ideal choice for practical implementation, opening the door for future hardware integration and enhancing efficiency and dependability in renewable energy systems.